(3QSGdI aj eYQaI GdaYd GdeDcO Hfhf GdJhcjO hGSJbUGA CMhGdg ef ZjQ eRjOs ((3eMeO Hf GdMSf GdHfGfj s)
(3ChdgG (B:s
(3hHYO, aGdbUO HgPG GdJbjjO, eYQaI GdaYd GdeDcO Hfhf GdJhcjO, hGSJbUGA CMhGdg ef ZjQ eRjO s
(3BNQgG (B:s
(3hjYjf ef GdQHGYj, hjNJGQ ef GdNeGSj, hjSJbje ef GdSOGSj abS Ydi Pdc, ced HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B82 - (3U(B85s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B139 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(1032 (3O(B) s
Keywords: (3GdfMhs